Identification of mare milk adulteration with cow milk by liquid chromatography-high resolution mass spectrometry based on proteomics and metabolomics approaches. (30th March 2023) - Ji, Zhongyuan; Zhang, Junyu; Deng, Chunxia; Hu, Zhisheng; Du, Qijing; Guo, Tongjun; Wang, Jun; Fan, Rongbo; Han, Rongwei; Yang, Yongxin
Highlights: Changes in protein components of mare milk adulterated with cow milk investigated by DIA-based proteomics and metabolomics. Potential fingerprints of proteins and metabolites used to identify mare milk with cow milk at levels as low as 1%. Several proteins of caseins and histatherin were used to detect of cow milk in mare milk. Several metabolites of orotic acid were used to detect of cow milk in mare milk. Abstract: Mare milk (MM) production is lower than that of cow milk (CM), making it a premium product. Unfortunately, sellers adulterate MM with cheap CM to unscrupulously gain more profits. This study aimed to analyze MM adulteration with CM using proteomics and metabolomics. Using univariate and multivariate statistical analysis, the relative abundances of certain proteins of caseins and secretoglobin family 1D member were found to be higher with a higher CM admixture percentage. In addition, several metabolites, such as orotic and 4-aminonicotinic acids, increased in the mare-cow milk mixture with an increased CM percentage. Accordingly, these proteins and metabolites distinguished MM adulterated with CM at levels as low as 1 %. These findings can serve as the basis for clarifying the differences at the proteome and metabolome in milk from minor dairy animals and ensure milk authenticity.